Diplomasi Perdagangan Indonesia dalam Rantai Pertambahan Nilai Global Produk Tekstil ke Pasar Timur Tengah - Yekti, Septian Nur (POLITEA, 2018)
Indonesia Trade Diplomacy in the Textile Product Global Value Chains to the Middle East Market. Textile and textile products are important commodities for all developing countries, including Indonesia. Despite of those significance, developing countries have to deal with the challenge of the global context. The crisis in developed countries previousely were major textile export destination add the challege. This paper aims to find out Indonesia’s strategy to maintain its textile industry as its major potential commodity. In doing so, this research focuses on the strategy of trade diplomacy in the context of global value chains. Considering the decline trend of export to the developed countries, this research focus on the market of Middle East as the non-traditional market. This reseach applies descriptive qualitative reseach metodh with the concept of global value chains and trade diplomacy as the research analitical framework. This research finds that, in the context of GVC, Indonesia has the highly competitive barrier to entry suitable to penetrate Middle East market. It has production chains domestically, while marketing chains to the Middle East countries. Furthermore, in trade diplomacy, Indonesia implements the function of representation, negotiation, and advocacy.Keywords:                Textile products export, GVC, trade diplomacy, Middle East market